Through the years with on-a-chip gas chromatography: a review. Issue 12 (21st June 2015) - Haghighi, F.; Talebpour, Z.; Sanati-Nezhad, A.
<x xml:space="preserve">Abstract</x> In recent years, the need for measurement and detection of samples in situ or with very small volume and low concentration (low and sub-parts per billion) is a cause for miniaturizing systems via microelectromechanical system (MEMS) technology.